2006
DOI: 10.4269/ajtmh.2006.74.425
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Onset of Transmission-Reducing Antibodies in Javanese Migrants Exposed to Malaria in Papua, Indonesia

Abstract: Transmission of Plasmodium falciparum malaria is initiated by sexual stages in the mosquito. Anti-Pfs48/45 and anti-Pfs230 sexual stage antibodies that are ingested together with parasites can reduce parasite development and subsequently malaria transmission. Acquisition of sexual stage immunity was studied in a cohort of 102 non-immune Javanese individuals migrating to hyperendemic Papua Indonesia. Seroprevalence of antibodies against Pfs48/45 and Pfs230 and functional transmission-reducing activity (TRA) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…As in previous studies (6,9,18,23,26,43,44), we found evidence for naturally acquired immunity against P. falciparum sexual stages. Overall, 22 to 28% of our samples were positive for sexual stage-specific antibodies, while 54 to 65% were positive for preerythrocyte-and asexual blood stage-specific antibodies.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…As in previous studies (6,9,18,23,26,43,44), we found evidence for naturally acquired immunity against P. falciparum sexual stages. Overall, 22 to 28% of our samples were positive for sexual stage-specific antibodies, while 54 to 65% were positive for preerythrocyte-and asexual blood stage-specific antibodies.…”
Section: Discussionsupporting
confidence: 72%
“…However, the seasonality of sexual stage-specific immune responses (28) has been rarely studied, making any comparison difficult. The importance of recent exposure to infection for the acquisition of sexual stage-specific immunity has been reported from previous studies in which the prevalence of anti-Pfs48/45 and anti-Pfs230 antibodies increased in migrants from an area of nonendemicity to an area of endemicity (9) and where functional transmission-reducing immunity was shown to increase during the transmission season (12). We did not determine functional transmission-reducing immune responses in the current data set.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) reported that the antibody response to Pfs230 is boosted by exposure to gametocytes. To date, most of those studies used the sandwich ELISA method using anti-Pfs230 MAbs in combination with cultured P. falciparum gametocyte crude lysates (2). In the case of TBV application in future field trials, seroepidemiological surveillance of such naturally existing transmission-reducing immunity seems to be essential; however, the availability of crude parasite antigen for such a large-scale study is one of the hurdles to be overcome.…”
Section: Discussionmentioning
confidence: 99%